Multi-criteria analysis of the Baltic banks from client attraction and profit generation perspectives - Kriščiukaitytė, Karolina; Baležentis, Tomas; Štreimikienė, Dalia (Journal of Business Economics and Management, 2025)
The economic and regulatory environment banks operate in poses challenges in regard to different facets of sustainability and requires proper managerial and technological innovations. Bank performance can be analysed from various viewpoints. Therefore, it is important to develop comprehensive frameworks for assessment of banking performance. The paper develops a twostage approach for measuring banking performance from the client attraction and profit generation perspectives. The multi-criteria framework involving three multi-criteria decision-making methods is developed to ensure robustness of the results. The empirical research deals with the 17 commercial banks operating in the three Baltic States. This case is interesting as it covers a low-interest-rate environment. While Lithuanian banks excelled in the client attraction perspective, the results for 2017–2021 suggest that they should focus on the improvement of performance in this regard and profit generation if compared to banks operating in Latvia and Estonia.